(3GdaSQ aj TQM OjhGf GdeJfHjs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3SCdJ, GOGe Gddg JSOjOc Cf GUfY dc TYQ CHj GdWjH CMeO Hf GdMSjf GdeJfHF jaSQ eYGfjg s
(3BNQgG (B:s
(3fXQI GdjYe hGdYjf oScQi aUGQJ cdgG ddOeY eBakG s
(3fSNI KGdKIs
(3JeGe GdfSNI aj bSejf JJab aj ChdgG eY GdfSNI GdChdi eY GNJdGa aj HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
Keywords: (3GdCOHs